Curriculum Cardiology: From the Academy of the German Cardiac Society Curriculum Kardiologie: Aus der DGK-Akademie - Bauersachs, J.; Aßmus, B.; Baldus, S.; Billig, H.; Breitbart, P.; Bongarth, C. M.; Buerke, M.; Diller, G. P.; Dörr, O.; Dörr, R.; Duncker, D.; Eckardt, L.; et al. (Die Kardiologie, 2026)
The current update of the “Curriculum Cardiology” of the German Cardiac Society (DGK) first compiled in 2013 and updated in 2020 was performed during the discussions on the revision of the education program for cardiologists of the German Medical Association published in 2018. Cardiology continues to substantially develop further in all fields and numerous certifications for specialization within cardiology are issued by the German Cardiac Society (DGK). The goal of this curriculum is to summarize from the view of the German Cardiac Society which competencies cardiologists should nowadays have. In addition to the increasing specialization within cardiology, it is also essential to have a common fundament of cardiology embedded in the broad field of internal medicine. This indispensable fundament of cardiology consists of a basic stock of theoretical knowledge, practical skills (level of competence I‑III) and professional behavior and attitudes of (prospective) cardiologists. This core curriculum for general cardiologists should enable the cardiology trainee to configure the further education time as efficiently as possible and subsequently to maintain and expand the knowledge gained in the sense of a “lifelong occupational” qualification. The individual components of further education are: (1) basic cardiological examination, (2) general cardiology, (3) cardiac imaging, including echocardiography, cardiac magnetic resonance imaging, computed tomography and nuclear cardiology, (4) electrophysiology, (5) catheter-based diagnostics and treatment of congenital and acquired diseases of the heart and vessels (cardiac catheterization diagnostics and interventions), (6) cardiovascular intensive care and emergency medicine, (7) digital cardiology. This curriculum is intended to reach not only trainees in cardiology but also cardiologists as trainers and also the German Medical Associations, to show them which contents and skills as well as behavior and attitudes should be transmitted to trainees according to the education criteria of the German Cardiac Society. Since the 2020 update of the curriculum a new chapter in further education on “digital cardiology” has been added for a better representation of this rapidly evolving area. The competence of cardiologists in cardiovascular imaging is still essential. Only multimodal crosslinking of the cardiac imaging with the pillars “echocardiography”, “magnetic resonance imaging”, “computed tomography” and “nuclear cardiology” with the clinical competence enables an optimal treatment of cardiac patients.
CRIS-Team Scopus Importer:2026-04-17
Keywords: Angiology; Cardiomyopathy; Cardiovascular disease; Diagnostics; Digital cardiology; Gender medicine; Heart failure; Intensive care and emergency medicine; Interventional cardiology; Prevention; Psychocardiology; Rhythmology; Structural heart diseases; Treatment